Information and dataset system on the rehabilitation of degraded tropical forest ecosystems project for international network - Anazawa, M.; Sawada, H.; Kobayashi, S. (Center for International Forestry Research, 2001)
This information and dataset system aims to facilitate international exchange and synthesis of the scientific and technical information based on results of the CIFOR/Japan project on the rehabilitation of degraded tropical forest ecosystems. There are two main pathways. One path integrates general information at the study site from annual reports, site map, remote sensing data, aerial chart and vegetation map into plot data of each site. Their outputs are data on site condition, vegetation, soil, climate, etc. which are accessible to the public. Another path is to accumulate experimental raw data into “Download” the use of which is restricted and requires a password. Version 1 of this system is experimentally located on the website at: http://www.ffpri.affrc.go.jp/labs/fmrt/cifor/start.htm